Aplikasi Sistem Pendaftaran Jasa Pelatihan Setir Mobil Berbasis Web Pada LPK DELTA Kulon Progo - Dwi Rena Gasik Pawestri; Nani Purwati; Lina Ayu Safitri (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2019)
The registration process on LPK DELTA is still done by coming directly to the office to register as a member. This is an obstacle for applicants whose regions are outside Kulon Progo. Another problem is that there is often an error in scheduling steering wheel training and obstacles in the storage process because it requires a large amount of storage space. This web-based car steering course application is the right solution to solve the problems that exist in LPK DELTA. In designing the steering wheel course system, this method uses research methods, namely data collection methods such as observation, interviews, literature studies and waterfall development methods. This steering wheel course application uses XAMPP software, Adobe Dreamweaver CS6 and uses programming languages such as HTML, PHP, CSS, and JavaScript. Testing this website using blackbox testing. From the results of the writing it can be concluded that the existence of this website as a medium of information and promotion to users and can facilitate the registration system and confirmation of payment of car steering training services online, minimize errors in registration, course scheduling, and accumulation of registration files because they are well managed and stored in the company database.